Knowledge & Perceptions of ICDS Anganwadi Workers with Reference to Promotion of Community Based Complementary Feeding Practices in Semi Tribal Gujarat - Parikh, Purvi; Sharma, Kavita (National Journal of Community Medicine, 2011)
Objective: To assess ICDS anganwadi workers’ knowledge and perception regarding promotion and enhance community based complementary feeding practices. Methodology: Total 17 anganwadi workers’ (AWWs) from one semi tribal sector (covering approximately 850 children under three two years) of Vadodara district in Gujarat state, India were purposely selected. This study employed interview with AWWs as a principal method of data collection using a pretested semi-structured interview schedule. The entire interview was divided into 8 themes. Results: The knowledge of AWWs with regard to key IYCF practices was average. None of the AWWs knew the complete rationale for promoting breastfeeding till 2 years and beyond. Merely 65% AWWs recommended food with thick consistency while 47% recommended liquid diets for children. These practices in fact are one of the primary reasons which can be attributed to low energy and protein intake during complementary feeding. As low as 18% AWWs advised giving small frequent feeds during illness and only 6% advised additional meal after illness. None of the AWWs recommended persistence in feeding the child with required quantity of food. Total 41% listed sickness as key reason for child not feeling hungry, missing out on the other two imperative reasons i.e. micronutrient deficiency and mouth lesion. Conclusion: Overall knowledge and perceptions for promoting of community based CF practices was average amongst the ICDS AWWs with a percent score of 40%. The AWWs were aware of key IYCF practices, however the AWWs perceptions and knowledge with regard to the rationale applicable to the appropriate recommended CF practices being promoted was rather poor. This is noted to be a critical gap and needs to be addressed for equipping the ICDS frontline workers for effectively promoting successful adoptions of CF practices by community.